Immediate Outcomes in Neonates Born to Diabetic Mothers - Sah, Vijay Kumar; Yadav, Sunil Kumar; Giri, Arun; Singh, Sandip Kumar (Journal of Nobel Medical College, 2023)
Background: Infants born to diabetic mothers are at a higher risk of developing complications like macrosomia, hypoglycemia, hypocalcemia, hypomagnesemia, polycythemia, hyperbilirubinemia, prematurity, transient tachypnea of newborn, respiratory distress syndrome, birth asphyxia, congenital heart diseases etc. The predominant causes of mortality are congenital anomaly, birth trauma, respiratory distress syndrome, prematurity and unexplained still birth. Hence this present study was conducted to study the incidence of complications among neonates of diabetic mothers. Materials and Methods: This was hospital-based observational study conducted in NICU and postnatal ward of a tertiary care hospital among 55 neonates. A detailed maternal history and complications during labor were recorded. Investigations like glucose estimation, PCV, serum calcium, serum bilirubin were done. The incidence of complications was assessed in terms of frequency and percentage. Results: Complications related to maternal diabetes were observed among 33 (18.15%) neonates. They were hypoglycemia, hypocalcemia, hyperbilirubinemia and polycythemia. Among them, hypoglycemia was the most common complication observed among 13(23.63%) neonates followed by hyperbilirubinemia among 10 (18.18%) neonates. Conclusion: Hypoglycemia was the most common complication followed by hyperbilirubinemia among infants born to diabetic mothers.